Viver é melhor que sonhar : Quadrilha Junina Unidos em Asa Branca e a pandemia da COVID-19 - Novais, Josiane Alves Barreto (2023)
The aim of this research is to analyze the dynamics and the transformations on the festive rituals of the quadrilhas juninas of Aracaju-SE during the Covid-19 Pandemic. By this, I try to understand the experiences of the quadrilhas regarding the absences of festive rituals due to the Pandemic, trying to comprehend the memories, practices and meanings associated with the quadrilhas juninas. Among the objectives of this dissertation, I try to highlight what was accomplished by the quadrilhas during that time without presentations, to understand the meanings of absence and relationships of sociability in their most traditional formats for the quadrilheiros and quadrilheiras of Aracaju during the Pandemic, to analyze the meanings the reframing of the June festival in the period of the quarantine and its return to the “arraias”. For this, I take as empirical reference the Quadrilha Junina Unidos de Asa Branca, because it is considered one of the oldest quadrilha junina of the Sergipe cultural scene. In this research, I used participant observation and my experience and relationship as a quadrilheira since 1997. With this, I hope that this study can help to a understand the importance of the festive rituals in our and of the always rich and complex processes of re-elaboration of artistic and cultural dynamics in the field of the quadrilhas juninas.